2021
DOI: 10.3390/agronomy11091859
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Mineral Nutrients, Photosynthesis and Related Physiological Parameters of Citrus in Response to Nitrogen Deficiency

Abstract: Limited data are available on the physiological responses of Citrus to nitrogen (N) deficiency. ‘Xuegan’ (Citrus sinensis (L.) Osbeck) and ‘Shantian pummelo’ (Citrus grandis (L.) Osbeck) seedlings were fertilized with nutrient solution at a N concentration of 0, 5, 10, 15 or 20 mM for 10 weeks. N deficiency decreased N uptake and N concentration in leaves, stems and roots and disturbed nutrient balance and homeostasis in plants, thus inhibiting plant growth, as well as reducing photosynthetic pigment levels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 75 publications
3
37
0
Order By: Relevance
“…Moreover, the application of N fertilizers is usually excessive [ 2 ]. The world N fertilizer application increased from 11.4 Tg year − 1 in 1961 to 107.7 Tg year − 1 in 2019 [ 3 ]. Reducing the application of N fertilizers without affecting crop yield is an urgent challenge for agriculture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the application of N fertilizers is usually excessive [ 2 ]. The world N fertilizer application increased from 11.4 Tg year − 1 in 1961 to 107.7 Tg year − 1 in 2019 [ 3 ]. Reducing the application of N fertilizers without affecting crop yield is an urgent challenge for agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon partitioning between roots and shoots is one of the major factors determining shoot growth [ 11 ]. Most experiments under controlled or field conditions showed that N-deficiency increased the partitioning of C to roots, thus increasing the ratio of root/shoot (R/S) [ 3 , 12 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The global population was expected to reach 9.6 billion by 2050, which required crop yields to increase by more than 85% compared to 2013 (Mu and Chen, 2021); an increasing amount of fertilizers was therefore used in modern agricultural crop production to meet the requirements of the rapidly escalating population for crop yield and quality (Waqas et al, 2021;Zhu et al, 2020). The amount of N fertilizers applied globally had increased 10-fold in the past 60 years (Huang et al, 2021), and the K fertilizer requirements in China had far exceeded mined K resources (Li et al, 2021d), which not only caused pollution, destruction of ecological balance and soil nutrients but also had a huge impact on human economic benefits and health (Chen et al, 2018;Sabzi et al, 2021). Therefore, investigating the response of crops to NK and balancing fertilizer application are the bases of the need to balance benefits and costs and avoid environmental degradation (Huang et al, 2021;Li et al, 2021c;Zhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of N fertilizers applied globally had increased 10-fold in the past 60 years (Huang et al, 2021), and the K fertilizer requirements in China had far exceeded mined K resources (Li et al, 2021d), which not only caused pollution, destruction of ecological balance and soil nutrients but also had a huge impact on human economic benefits and health (Chen et al, 2018;Sabzi et al, 2021). Therefore, investigating the response of crops to NK and balancing fertilizer application are the bases of the need to balance benefits and costs and avoid environmental degradation (Huang et al, 2021;Li et al, 2021c;Zhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated N-deprivation significantly decreased the CO 2 assimilation of plants including tea and citrus [ 21 , 22 ]. In the present study, the global metabolic profiles of N-deficient leaves and roots based on an untargeted metabolomics approach were discussed.…”
Section: Introductionmentioning
confidence: 99%